Multistable Phase Locking Patterns in a Bursting Neural System - Seon-Hee Park; Young-Sup Hwang; Jae-Hun Choi (Journal of Systemics, Cybernetics and Informatics, 2003)

(untitled)
We quantitatively analyze the multistability of dynamic patterns of a busting neural system with diffusive coupling. Through effective coupling analysis, we show that the system is not in-phase locking but exhibits various phase locking patterns, each of which corresponds to the stable fixed points of the effective coupling. The simulation proves the validity of the effective coupling method in analyzing the multistability of neural systems which presents complicated dynamic patterns such as bursting.